192 Agulhas: Narrativas Transversais - Soares, Luan Daniel Coelho; Silva, Cláudia Maria França da (Farol, 2023)
Course and analysis of an artwork related to the experimental research of the current master’s degree, which seeks to link Tattoo and Contemporary Drawing, from their materials, techniques, supports and gestures. The process of creating the work “192 Agulhas” began with an inventory of objects that constitute my surroundings, and that, in a way, define me as choices and actions in the world. From the inventory, an industrial object was chosen from this list, elaborating, from or with it, operations of functional or formal derealization, serialization, enigmatization or even erasure of the object.